Teaching Business English Correspondence for Export-Oriented SMEs - Eriklex Donald; Irma Rahmawati; Alhazami, Lutfi (JPM: Jurnal Pengabdian Masyarakat, 2024)
This community service is carried out to develop business competence and entrepreneurial English among MSMEs who carry out exports. The entrepreneurs selected are Small and Medium Industrial Entrepreneurs assisted by the Tomohon City Industry and Trade Service. Community service partners are 1. Manado City Industry and Trade Service. 2. Tomohon City Industry and Trade Service 3. Bitung City Industry and Trade Service 4. Creative Innovative Entrepreneurs Association 5. Dian Nusantara University Export-Import Center. From the situation analysis carried out, it appears that the problem faced by partners is a lack of English language skills and correspondence in English because of the basic assumption that English is a difficult subject. From the pretest carried out there were several basic business materials that were difficult to understand, especially reading, lack of understanding of topics, main ideas, and answering WH Questions as well as entrepreneurs' lack of focus in following the learning process. Teaching uses a motivational persuasive communication approach, holding initial tests, teaching topics, main ideas, and WH Questions with material enrichment. After the treatment process, an evaluation test (post test) was held which showed that the entrepreneurs were starting to be motivated to learn English, focused and independent with good average test results. The contributions and benefits obtained by the target audience are motivation to learn Reading, focus and independence in learning English to support correspondence for export.